Identification and characterization of pathogens causing saffron corm rot in China - Ren, Tingdan; Dai, Dejiang; Yu, Miao; Li, Tao; Zhang, Chuanqing (Frontiers in Microbiology, 2023)
Corm rot is the most important disease of saffron, for which fungi from several genus such as Fusarium spp. Penicillium spp. and Botrytis spp., have been previously reported to be the pathogens. It is treated as a typic soil-borne disease until present and therefore the“saffron-rice”rotation was adopted as the main technique for the management and which don’t get satisfied efficacy. In this research, we used a combination of amplicon sequencing and traditional isolation methods to identify the causal agents, main infection source. The diversity of microbial communities in diseased saffron corms and soil decreased significantly compared with healthy corms and soil. The contents of Penicillium and Botrytis in healthy and diseased corms were similarly high, indicating that them were not directly related to the occurrence of corm rot. But the relative abundance of Fusarium, Cadophora and Fusicolla were significantly higher in the diseased corms than healthy ones. The abundance of Fusarium increased, while the abundance of Oidiodendron, Paraphaeosphaeria and the endophytic beneficial bacteria Pseudomonas decreased, which may relate to the occurrence of the disease. The co-occurrence network diagram showed that the correlation between fungal and bacterial communities was mainly positive. Plant pathogens were relatively abundant in the diseased soil, according to functional gene prediction. At the same time, we also collected 100 diseased corms from the fields in Jiande, where is known as the “hometown of saffron”. All isolated pathogenic strains were identified as Fusarium oxysporum through morphological observation and phylogenetic tree analysis of ITS, Tef-1α and β-tubulin. To better clarify the biological characteristics of F. oxysporum, we cultured the isolates at different temperatures and pH values. The optimum temperature for mycelial growth and sporulation was 25°C , pH 6，carbon sources sorbitol and nitrogen sources, peptone. In short, our results suggests that F. oxysporum was the pathogen causing corm rot in Jiande and corms other than soils are the main primary infection source. These new understanding of saffron corm rot will provide the theoretical basis for its better and efficiently management.